2002
DOI: 10.1677/joe.0.1740299
|View full text |Cite
|
Sign up to set email alerts
|

Insulin increases the density of potassium channels in white adipocytes: possible role in adipogenesis

Abstract: We studied the potassium currents in white adipocytes obtained by culturing preadipocytes from rat epididymal tissue, both with insulin (WA i ) and without insulin (WA o ), in order to test the role of insulin in the development of voltage-gated potassium channels (K v ) during adipogenesis. Occasionally, very small potassium currents (I K,V ) were present in preadipocytes; however these currents were measured in all differentiated cells (adipocytes). WA i exhibited greater macroscopic potassium currents than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…22,23 In contrast to smooth muscle cells, K v channels in adipocytes are rapidly-inactivating, sensitive to TEA, 24 -26 and relatively resistant to 4-AP. [27][28][29] Ba 2ϩ -sensitive inward rectifying K ϩ have not been detected in adipocytes. In addition, we found that the intracellular membrane potential was more negative in smooth muscle cells of (ϩ) fat rings compared with (Ϫ) fat rings, a difference that was abolished by 4-AP.…”
Section: Discussionmentioning
confidence: 92%
“…22,23 In contrast to smooth muscle cells, K v channels in adipocytes are rapidly-inactivating, sensitive to TEA, 24 -26 and relatively resistant to 4-AP. [27][28][29] Ba 2ϩ -sensitive inward rectifying K ϩ have not been detected in adipocytes. In addition, we found that the intracellular membrane potential was more negative in smooth muscle cells of (ϩ) fat rings compared with (Ϫ) fat rings, a difference that was abolished by 4-AP.…”
Section: Discussionmentioning
confidence: 92%
“…We demonstrated the mean HDL-C (TT: 1.65 versus CC: 1.67, P  = 0.47) was lower and LDL-C (TT: 2.72 versus CC: 2.63, P  = 0.46) was higher in the population with a TT genotype than those with a CC genotype, which may provide some clues for future investigation on how rs1051295 genotype TT might influence fat metabolism. In support of a role of Kv channels in adipocyte metabolism, Kv channel activity has been recorded in human adipocytes [26], which responded to insulin by increasing channel density [27]. However, the specific Kv isoform or its downstream actions in adipocytes have not been critically assessed, thus requiring much further study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, TEA has been shown to inhibit the differentiation of white adipose cells from preadipocytes, suggesting the involvement of Kv channels in adipogenesis in these cells, although specific K + channel subtypes were not defined [9] . Therefore, expression of Kv channels in undifferentiated cells and alterations in Kv channels during differentiation may somehow be involved in the differentiation process.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors are critical for differentiation of hMSCs along a particular lineage, including cell density, mechanical forces, and multifactorial stimulation with specific nutrients [3][4][5][6][7] . For example, insulin, insulin-like growth factor I, glucocorticoids, and other growth hormones are known to be essential for adipogenic differentiation in vitro [2,4,[7][8][9] . Voltage-gated K + (Kv) channels are important in maintain-ing cellular excitability in neurons and muscle cells.…”
Section: Introductionmentioning
confidence: 99%